2016
DOI: 10.1590/0034-7167.2016690111i
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da implantação do programa de assistência às pessoas com hipertensão arterial

Abstract: Objective: to evaluate the implementation of the care program for people with hypertension in Maringá-PR. Method: it is an evaluative research of cross-sectional design. Data were collected through structured interviews with 63 nurses between April and June 2013. Results: as missing or insuffi cient, there were: transportation for outside activities; work equipment; educational materials; training resources; inclusion of the family in the care plan; risk classifi cation of individuals; determination of therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
(19 reference statements)
0
7
0
9
Order By: Relevance
“…Estudo com 63 enfermeiros de ESFs identificou problemas na assistência relacionado à estrutura física e organizacional e na capacitação de recursos humanos. 24 Outro estudo de abordagem qualitativa notificou resultado semelhante. 25 Portanto, os programas de gestão de doenças devem se adaptar e caminhar com os avanços tecnológicos e mudanças nas demandas dos indivíduos, a fim de reduzir as desigualdades de acesso aos serviços de saúde.…”
Section: Discussionunclassified
“…Estudo com 63 enfermeiros de ESFs identificou problemas na assistência relacionado à estrutura física e organizacional e na capacitação de recursos humanos. 24 Outro estudo de abordagem qualitativa notificou resultado semelhante. 25 Portanto, os programas de gestão de doenças devem se adaptar e caminhar com os avanços tecnológicos e mudanças nas demandas dos indivíduos, a fim de reduzir as desigualdades de acesso aos serviços de saúde.…”
Section: Discussionunclassified
“…With respect to the work processes, the unsatisfactory level of knowledge of the technician due to insufficient training, the negligent professional behavior in following the recommendations on BP reading due to lack of supervision, or shortage of professionals who conduct multiple activities could explain the omission of this procedure 21,22 . Silva et al 23 identified the lack of adequate cuffs in 85% of units and lack of training in approximately 75% of nursing professionals from the PHC at the SUS in Maringá, Paraná.…”
Section: Discussionmentioning
confidence: 99%
“…We emphasize that the sub-dimension of health promotion involves actions since it entails actively seeking new cases and strategies to stimulate healthy habits, up to the establishment of goals for the follow-up of individuals with hypertension. (11) However, the sub-dimension of individualized care involves such actions as medical consultations and nursing consultations according to protocols, cardiovascular risk classification, and home visits to users who do not adhere. (11) However, even with the proposition of reorganizing care to individuals with chronic conditions, from the national literature, we verified that implementation of innovations in care are still occurring in an incipient form.…”
Section: Discussionmentioning
confidence: 99%
“…(11) However, the sub-dimension of individualized care involves such actions as medical consultations and nursing consultations according to protocols, cardiovascular risk classification, and home visits to users who do not adhere. (11) However, even with the proposition of reorganizing care to individuals with chronic conditions, from the national literature, we verified that implementation of innovations in care are still occurring in an incipient form. In an evaluative study among 13 health units in the South region of Brazil, at two different times among teams and users of the services, we observed that incorporation of self-care plans for individuals with chronic conditions is weak -many professionals did not monitor the plans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation